Avant-garde in Panoramic View - Nowicka, Daria (Poznańskie Studia Slawistyczne, 2020)
The Seeing Avant-garde [Widzenie awangardy] volume edited by Agata Stankowska, Marcin Telicki and Agata Lewandowska is a collection of the articles about the avant-garde update. Written by many researchers, the articles show a wide scale of research on the contemporary avant-garde manifested in literature, art, music, theatre and cybernetics. As an extremely valuable publication, the book in question concentrates on the new and original methods of comparative research, marks new reading directions, and presents contemporary problems of aesthetics.